Increased Glucose Availability Attenuates Myocardial Ketone Body Utilization. Issue 15 (4th August 2020) - Brahma, Manoja K.; Ha, Chae‐Myeong; Pepin, Mark E.; Mia, Sobuj; Sun, Zhihuan; Chatham, John C.; Habegger, Kirk M.; Abel, Evan Dale; Paterson, Andrew J.; Young, Martin E.; Wende, Adam R.
Abstract : Background: Perturbations in myocardial substrate utilization have been proposed to contribute to the pathogenesis of cardiac dysfunction in diabetic subjects. The failing heart in nondiabetics tends to decrease reliance on fatty acid and glucose oxidation, and increases reliance on ketone body oxidation. In contrast, little is known regarding the mechanisms mediating this shift among all 3 substrates in diabetes mellitus. Therefore, we tested the hypothesis that changes in myocardial glucose utilization directly influence ketone body catabolism. Methods and Results: We examined ventricular‐cardiac tissue from the following murine models: (1) streptozotocin‐induced type 1 diabetes mellitus; (2) high‐fat‐diet–induced glucose intolerance; and transgenic inducible cardiac‐restricted expression of (3) glucose transporter 4 (transgenic inducible cardiac restricted expression of glucose transporter 4); or (4) dominant negative O ‐GlcNAcase. Elevated blood glucose (type 1 diabetes mellitus and high‐fat diet mice) was associated with reduced cardiac expression of β‐hydroxybutyrate‐dehydrogenase and succinyl‐CoA:3‐oxoacid CoA transferase. Increased myocardial β‐hydroxybutyrate levels were also observed in type 1 diabetes mellitus mice, suggesting a mismatch between ketone body availability and utilization. Increased cellular glucose delivery in transgenic inducible cardiac restricted expression of glucose transporter 4 mice attenuated cardiac expression of both Bdh1 and Oxct1 and reduced rates of myocardial BDH1 activity and β‐hydroxybutyrate oxidation. Moreover, elevated cardiac protein O ‐GlcNAcylation (a glucose‐derived posttranslational modification) by dominant negative O ‐GlcNAcase suppressed β‐hydroxybutyrate dehydrogenase expression. Consistent with the mouse models, transcriptomic analysis confirmed suppression of BDH1 and OXCT1 in patients with type 2 diabetes mellitus and heart failure compared with nondiabetic patients. Conclusions: Our results provide evidence that increased glucose leads to suppression of cardiac ketolytic capacity through multiple mechanisms and identifies a potential crosstalk between glucose and ketone body metabolism in the diabetic myocardium.